Ovlivňuje světová zbrojní výroba politický vývoj nebo naopak? (Czech Journal of International Relations, 2000)
One of the most ancient human professions (the defence of life and hunting) has gradually changed into a technically most demanding engineering industry, especially in the 20th century; this also places great demands on the standard of production and is economically most lucrative: it is arms production. This industry influences a number of other civilian professions which gradually take over the most progressive know-how and technology from this industry.The volume and types of the manufacture of weapons are as a rule determined by the consumer; this is done by purely political bodies – parliaments and governments – which approve military concepts and resources for military budgets and, consequently, also the finances earmarked for the purchase and development of new arms and weapons systems. That is why the arms manufacturers at times lobby politicians and the pertinent political institution in support of higher funds for the purchase of weapons, or else they engage in various provocations to incite major or minor conflicts. Such conflicts are then impatiently solved by military means which adds to a further increase in arms production and the development of constantly more destructive weapons that can be tested in such conflicts.The United Nations Organization came into being in 1945 for the purpose of preserving and consolidating peace and security and promote cooperation among states; it contributed to a large extent to limiting the threatening number of conflicts in the world, and thereby to restraining arming. Unfortunately, the Cold War begun to expand simultaneously, accompanied by increasing arms production. The author documents this by a multitude of revealing facts and figures including data on the globalization and merger of arms concerns.The author further deals with arms exports by the major manufacturers. He notes in this connection that the most advanced countries generally do not export their latest military technology. The biggest importer is now Saudi Arabia and other Near East countries as well as countries in Asia. The author supplements these facts by a prognosis up to the year 2015.The author tries to find an answer to the question: Whom does this serve? Who benefits by a conflict of war? Quoting the recent example of the Balkans, he demonstrates that war can benefit exclusively arms and ammunition manufacturers to whom it means spiraling profits. In the context of the wars in the Balkans, the author also discusses such questions as the creation of a new military concept by Russia, China, and the North Atlantic Alliance in the 21st century as well as issues related to demands for newly developed weapons.